THE EFFECT OF PERCEIVED ORGANIZATIONAL SUPPORT AND WORKLOAD ON JOB SATISFACTION THROUGH WORK-SCHOOL CONFLICT AS A MEDIATING VARIABLE - Lubis, Feri; Nurhayati, Mafizatun (Dinasti International Journal of Management Science, 2020)
This study aims to examine and analyze the effect of perceived organizational support and workload on job satisfaction through work school conflict as a mediating variable. Respondent data is taken from Master students with status as employees who study at universities that have A accreditation in DKI Jakarta. The sampling method used in this study was purposive sampling. The population is taken using the Hair method in which the number of indicators is multiplied (5-15) (53 x 5) so that 265 samples are obtained). The analytical method used in this study is SEM-PLS 3.0. The results showed that the perception of organizational support had a positive and significant effect on satisfaction but did not affect work school conflict. Workload has a negative effect on satisfaction and a positive and significant effect on work school conflict. Work school conflict plays a role in mediating the effect of perceived organizational support on job satisfaction. In addition, workload plays a role in mediating the effect of perceived organizational support on job satisfaction